2021
DOI: 10.1186/s13031-021-00344-x
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening healthcare providers’ capacity for safe abortion and post-abortion care services in humanitarian settings: lessons learned from the clinical outreach refresher training model (S-CORT) in Uganda, Nigeria, and the Democratic Republic of Congo

Abstract: Background Fragile and crisis-affected countries account for most maternal deaths worldwide, with unsafe abortion being one of its leading causes. This case study aims to describe the Clinical Outreach Refresher Training strategy for sexual and reproductive health (S-CORT) designed to update health providers’ competencies on uterine evacuation using both medications and manual vacuum aspiration. The paper also explores stakeholders’ experiences, recommendations for improvement, and lessons lear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…This result is in line with Hassan, [21] , who studied ''Nurses' Knowledge and Practice Regarding Post-Miscarriage Care in Omdurman Maternity Hospital, Khartoum State, Sudan '' and reported that most of the studied nurses had poor knowledge regarding the first intercourse Post-Miscarriage. Moreover, This result comes in agree with Tran et al, [22] , who studied ''Strengthening healthcare providers' capacity for safe abortion and postabortion care services in humanitarian settings: lessons learned from the clinical outreach refresher training model (S-CORT) in Uganda, Nigeria, and the Democratic Republic of Congo'' and reported that the knowledge of the health care provider had improved after the workshop. Regarding the knowledge about waiting time for second pregnancy after abortion, the present study illustrated that the minority of the studied nurses had good knowledge regarding the waiting time for second pregnancy after abortion increased to the majority of them immediately after application of guideline then decreased to be the most of them post guideline application.…”
Section: Discussionsupporting
confidence: 82%
“…This result is in line with Hassan, [21] , who studied ''Nurses' Knowledge and Practice Regarding Post-Miscarriage Care in Omdurman Maternity Hospital, Khartoum State, Sudan '' and reported that most of the studied nurses had poor knowledge regarding the first intercourse Post-Miscarriage. Moreover, This result comes in agree with Tran et al, [22] , who studied ''Strengthening healthcare providers' capacity for safe abortion and postabortion care services in humanitarian settings: lessons learned from the clinical outreach refresher training model (S-CORT) in Uganda, Nigeria, and the Democratic Republic of Congo'' and reported that the knowledge of the health care provider had improved after the workshop. Regarding the knowledge about waiting time for second pregnancy after abortion, the present study illustrated that the minority of the studied nurses had good knowledge regarding the waiting time for second pregnancy after abortion increased to the majority of them immediately after application of guideline then decreased to be the most of them post guideline application.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, no statistically significant relationship was found between gravida and the effectiveness of MVA in achieving complete evacuation. (13)(14)(15)(16).…”
Section: Resultsmentioning
confidence: 99%
“…NGOs and other organisations providing MA services frequently emphasise the inclusivity of their reach, for example, to those in humanitarian settings or to adolescents 18 , 52 . The adaptations highlight an opportunity for organisations to strengthen their focus, reach, and communication to engage with people in vulnerable settings and draw upon grassroots’ insights and strategies, such as partnership strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limiting CAC provision, the COVID-19 pandemic also created opportunities to expand services. Guided by past lessons from emergency-settings 18 and advances in telemedicine 19–25 , both international and national non-profit and non-governmental organisations (NGOs) in the field of SRH adapted their CAC programmes to maintain access to services, while keeping their clients, providers, and communities safe from COVID-19 26 . Furthermore, owing to efforts from SRH advocates, policymakers enacted innovative emergency SRH protocols to ensure safe continuity of CAC access within the COVID-19 restrictions 27 .…”
Section: Introductionmentioning
confidence: 99%